Piperlongumine Inhibits Akt Phosphorylation to Reverse Resistance to Cisplatin in Human Non-Small Cell Lung Cancer Cells via ROS Regulation - Zhang, Chao; He, Lian-Jun; Zhu, Yi-Bao; Fan, Qing-Zhu; Miao, Dong-Dong; Zhang, Sheng-Peng; Zhao, Wen-Ying; Liu, Xiao-Ping (Frontiers in Pharmacology, 2019)
Multidrug resistance (MDR) is a major concern when administering chemotherapy to patients with non-small cell lung cancer (NSCLC). MDR modulators are agents that can reverse MDR, thereby enhancing the chemosensitivity of tumor cells. Thus, their development will improve therapeutic efficacy in cancer. However, few effective MDR modulators have been identified to date. Piperlongumine (PL) has been shown to effectively reverse MDR in several types of cancers; however, the mechanisms associated with the MDR reversal effect of PL and its regulation of target factors in MDR cells are still unclear. This study investigated the reversal effect of PL both in vitro and in vivo and provided evidence that PL inhibited the phosphorylation of Akt via the accumulation of reactive oxygen species in MDR cells. Consequently various Akt activation-dependent genes caused a reduction of drug efflux and induction of apoptosis in cisplatin-resistant A549 NSCLC cells. These results indicate that Akt phosphorylation may play a functional role in the reversal effect of PL and contribute, at least in part, to the treatment outcomes of patients with MDR.